Detection of New Francisella-Like Tick Endosymbionts in Hyalomma spp. and Rhipicephalus spp. (Acari: Ixodidae) from Bulgaria - Ivanov, Ivan N. (American Society for Microbiology, 2011)

(untitled)
We report on the identification of two new Francisella-like endosymbionts (FLEs) found in three different tick species from Bulgaria. The FLEs were characterized by 16S rRNA and tul4 gene sequencing and seem to lack the molecular marker RD1. These two new taxa seem to be facultative secondary endosymbionts of ticks.